2014
DOI: 10.1118/1.4866224
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and simulations of focused beam for orthovoltage therapy

Abstract: Low energy focused x-ray beams could be used to irradiate tumors inside soft tissue within 5 cm of the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…A focused kV x-ray beam, however, could concentrate the dose within the tumor, several centimeters below the entry surface. 2 Since focusing would result in spreading the beam across the skin surface, lower energy photons may still be employed with desired skin sparing. Polycapillary focusing and collimating lenses are widely used in x-ray fluorescence and x-ray diffraction applications.…”
Section: Introductionmentioning
confidence: 99%
“…A focused kV x-ray beam, however, could concentrate the dose within the tumor, several centimeters below the entry surface. 2 Since focusing would result in spreading the beam across the skin surface, lower energy photons may still be employed with desired skin sparing. Polycapillary focusing and collimating lenses are widely used in x-ray fluorescence and x-ray diffraction applications.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a polycapillary-lens-focused kV x-ray beam could pass through a water equivalent medium and maintain focus at a target several cm below the entry surface. 37 A polycapillary x-ray lens consists of a large number of small hollow glass tubes. X rays are guided through these curved and tapered tubes by multiple total reflections, similar to those in light-transmitting fiber optics.…”
Section: B Focused Kv X-ray Treatmentmentioning
confidence: 99%
“…However, in the case where a tumour is extended in both traversal directions (x and y), a pure linear scan of the beam would cause a shift of the peak dose towards the phantom surface. This effect is due to the superposition of the beams and can be avoided by associating a rotation with each translation of the beam, as reported by Abbas et al (2014). So far, we have considered a target localized at a depth z f of 4.75 cm within the phantom.…”
Section: Tablementioning
confidence: 99%
“…This method requires a LINAC and could be used to focus photons within the energy range 0.4-4 MeV (Figueroa & Valente, 2015). A further approach to obtain a convergent X-ray beam for radiotherapy application consists of using an X-ray tube and a polycapillary lens as a focusing device (Mahato & MacDonald, 2010;Abbas et al, 2014). A polycapillary lens exploits multiple total reflections of X-rays inside many hollow glass channels to focus the photon beam towards a target.…”
Section: Introductionmentioning
confidence: 99%